Comparison of the Effects of Osteochondral Autograft Transplantation With Platelet-Rich Plasma or Platelet-Rich Fibrin on Osteochondral Defects in a Rabbit Model. (December 2017) - Maruyama, Masahiro; Satake, Hiroshi; Suzuki, Tomoto; Honma, Ryusuke; Naganuma, Yasushi; Takakubo, Yuya; Takagi, Michiaki
Background: Although osteochondral autograft transplantation (OAT) provides satisfactory outcomes for osteochondral defects, for large defects OAT is often inadequate because of graft availability. Osteochondral allograft transplantation is an alternative treatment for large defects, but this approach is limited by graft storage constraints and carries disease transmission risks. Platelet-rich fibrin (PRF) is a second-generation platelet concentrate, and its positive effect on articular cartilage has been reported. However, the effect of PRF with OAT of osteochondral defects is unknown. Purpose: To compare the effects of OAT with platelet-rich plasma (PRP) and PRF on osteochondral defects in a rabbit model. Study Design: Controlled laboratory study. Methods: Forty-two juvenile rabbits were divided into control, PRP, and PRF groups. In the control and PRP groups, a cylindrical osteochondral defect (5 mm in diameter and 2 mm in depth) was created on the patellar groove, and an osteochondral graft (3.5 mm in diameter and 5 mm in length) harvested from the contralateral side was inserted into the distal portion of the defect. After wound closure, either normal saline or PRP was injected in the knee. In the PRF group, a PRF clot was placed in the defect before grafting. The surgical site was macroscopically and histologically assessed after 3 and 12 weeks. Results: At 3 weeks, the PRF group (n = 8) was macroscopically healed compared with the other 2 groups (control, n = 7; PRP, n = 6) ( P < .005). Histologically, osteochondral graft cartilage of the PRF group had normal cellularity and higher amounts of safranin O staining relative to the other 2 groups ( P < .005). At 12 weeks, all 3 groups (n = 8 per group) were macroscopically healed with normal or nearly normal cartilage, and osteochondral graft cartilage was histologically hyaline cartilage. In contrast, the PRF group healed with hyaline-like cartilage at nongrafted defects, whereas the other 2 groups healed with fibrocartilage ( P < .001). Conclusion: OAT with PRF maintained hyaline cartilage, and the nongrafted defect healed with hyaline-like cartilage. Clinical Relevance: PRF has the potential to improve clinical outcomes of OAT used to treat osteochondral lesions.